Press freedom: a comparative study between Malaysia and The United Kingdom / Amirah Huzveen Mohd Parveen…[et al.] - Mohd Parveen, Amirah Huzveen; Alodin, Farrah Dina; Adam, Lisa Sofie; Ahmad Badawi, Mai Latulnadia (2009)
The title of this research is "Press Freedom" A Comparative Study between Malaysian and The United Kingdom". This research is done to address the limitations of press freedom. Recently, Malaysia's press had been rated as not free. Furthermore, there are a lot of incidents that happened which questioned the ability of press to do their works freely. The main reason for these problems is the restriction factors that had been practiced rigidly. We need to find the best solution to overcome these problems in order to avoid a greater harm to the Malaysian society. Since we do not have a specific law regarding press freedom in Malaysia, we need to look at other countries that have laws regarding press freedom. As to this research, we decided to compare Malaysia with the United Kingdom. From this, we can find the best solution on the most suitable way to be implemented in Malaysia. We also need to take into account few aspects such as the implementation and the enforcement in order to suit our society. In the end of this research, we will emerge with a few recommendations for the government to take action in order to uphold press freedom in Malaysia. We hope that with these recommendations press freedom can be uphold and change for the better in Malaysia.